The Serial Duplex Index Improves Differential Diagnosis of Acute Renal Transplant Dysfunction. (3rd April 2017) - Meier, Markus; Fricke, Lutz; Eikenbusch, Katrin; Smith, Emma; Kramer, Jan; Lehnert, Hendrik; Nitschke, Martin
Abstract : Objectives: Renal duplex sonography represents a standard noninvasive diagnostic procedure to demonstrate morphologic changes in acute kidney transplant dysfunction. We investigated whether a newly developed serial duplex index (SDI) can differentiate between acute cellular rejection and acute vascular rejection more effectively than the established Doppler parameters of the resistive index (RI) and pulsatility index (PI) in recently transplanted patients. Methods: Serial duplex scans of patients with histologically proven acute tubular necrosis (n = 25), acute cellular rejection (n = 28), acute vascular rejection (n = 18), and normal graft function (n = 50, partially protocol biopsied) were retrospectively analyzed. For each patient, the RI, PI, and cortex‐pelvis proportion (CPP) were included from the day of biopsy (t0) and 3 to 7 days before biopsy (t–1). The sequential CPP ratio (CPPt0 /CPPt–1 ), RI ratio (RIt0 /RIt–1 ), and PI ratio (PIt0 /Pit–1 ) were determined. The SDI was calculated as: RI ratio × PI ratio/CPP ratio. The diagnostic accuracy of the SDI was compared with that of the RI and PI ratios. Results: Selected groups were statistically comparable in all routinely determined transplant parameters. The SDI was significantly different between patients with normal graft function, acute cellular rejection, and acute vascular rejection ( P  < .01, analysis of variance on ranks), whereas the RI and PI ratios were only significantly different between patients with normal graft function and acute vascular rejection ( P  < .05, analysis of variance on ranks). The indices' ranges were defined by the 95% confidence intervals between the allograft functions. Conclusions: The developed SDI was able to detect acute renal transplant rejection with greater sensitivity and specificity than the RI and PI ratios. Since the SDI distinguishes between acute tubular necrosis, acute cellular rejection, and acute vascular rejection, it might be a supportive tool to indicate renal biopsy.